1999
DOI: 10.1021/jp9913665
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Rod-to-Vesicle Transition of Block Copolymer Aggregates in Dilute Solution

Abstract: The kinetics and mechanism of the rod-to-vesicle transition in aggregates of polystyrene310-b-poly(acrylic acid)52 diblock copolymers in dioxane/water mixtures are explored. The transition is induced by a jump in the water content from a point at which the morphologies are under equilibrium control. The transition mechanism is monitored by transmission electron microscopy (TEM). The transition intermediates are trapped by quenching solution samples to liquid nitrogen temperature and then preserving the aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
194
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(215 citation statements)
references
References 37 publications
19
194
0
2
Order By: Relevance
“…For PS-b-PAA a rod-to-vesicle transition was also observed by increasing the water content. It was proposed that those experimental results support mechanism 1 to explain vesicle formation [21].…”
Section: Polymersome Formationmentioning
confidence: 77%
See 1 more Smart Citation
“…For PS-b-PAA a rod-to-vesicle transition was also observed by increasing the water content. It was proposed that those experimental results support mechanism 1 to explain vesicle formation [21].…”
Section: Polymersome Formationmentioning
confidence: 77%
“…It was also shown that this approach can reproduce morphological transitions (micelles to cylinders to vesicles) by changing the interaction Flory-Huggin's parameter χ in the simulation, which reflects the change in solvent quality during the experiment [17]. The transition states created by a change in polarity of the solvent have been experimentally quenched and observed by TEM for polystyrene-block-poly(acrylic acid) block copolymer [21] and poly(ethylene oxide)-b-poly (3-(trimethoxysilyl) propyl methacrylate) (PEO-b-PTMSPMA) [22]. In both cases the addition of a selective solvent into polymer solution led to vesicular selfassembly.…”
Section: Polymersome Formationmentioning
confidence: 96%
“…The equilibrium between micellar assemblies and individual polymer chains involves a delicate balance of supramolecular polymerpolymer and polymer-solvent interactions, which provides a lever of enthalpic and entropic control (13) for the directed evolution of micellar morphologies with changes in the solution conditions. Studies to determine the kinetics of block copolymer micellization (14)(15)(16) and the kinetics and mechanisms for transformation of assembly morphologies (17)(18)(19) have become active areas of research. For a given block copolymer composition, the introduction of ions and alteration of the solution pH (20)(21)(22), modification of the solvent composition (23)(24)(25), and changes in the polymer concentration (26,27) have been found to effect reorganization of block copolymer supramolecular assemblies.…”
mentioning
confidence: 99%
“…The literature reports evidence similar phenomena, leading to the formation of spherical structures with a random-coil backbone conformation, for oligomers with large aromatic [58,59], dendritic [60] or amphiphilic [61,62] side groups. Analogously, rigid rodflexible coil block copolymers can self-assemble in selective solvents into specific nanostructures with morphology governed by the geometric disparity between the rod and coil segments and anisotropic interactions between rod blocks (formation of liquid crystalline or crystalline structures) [63,64]. The process described herein is not typical, since microparticles are formed by rigid molecules with relatively small side substituents.…”
Section: Dynamic Light Scattering Studies Of Ph-lpsq Micellesmentioning
confidence: 99%